History Page: Leaders in MSK Radiology - Kaur, Simranjeet; Lalam, Radhesh (Seminars in Musculoskeletal Radiology, 2022)
Charles Thurstan Holland was the first radiologist in the world and also the founder of the first radiology department. In the early days, radiographs were used primarily in the musculoskeletal system. Holland contributed significantly to the understanding of musculoskeletal radiology as seen on radiographs, including the appearance of ossification centers and accessory ossicles. The small triangular metaphyseal fragment in Salter-Harris type 2 fractures is called the “Thurstan Holland fragment.”
Keywords: Thurstan Holland fragment; first radiologist; first radiology department